Peran Komunikasi Internal Karyawan Dalam Meningkatkan Kinerja Di PT Jaya Kencanamas Farma - Deviani, Elmira; ., Suroso; Anggela, Flora Patricia (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
PT Jaya Kencanamas Farma, is a pharmaceutical health sub-distributor company that began operating in 2022. The objectives of this study include internal communication in the dimensions of internal communication, internal communication relationships or interactions, and barriers in internal communication. Using a descriptive qualitative approach research method, this research involves interviews, observations, and documentation studies as data collection methods and uses data source triangulation validity techniques. The results showed that internal communication in the company PT Jaya Kencanamas Farma has an important role in improving employee performance. The conditions of internal communication dimensions both vertically and horizontally at PT Jaya Kencanamas Farma are mutually sustainable to carry out work processes that are structural in nature, personal and group communication relationships are also carried out optimally to improve performance but there are major obstacles in internal communication in the form of miscommunication that occurs due to lack of clarity in the direction of communication and message interpretation. Various efforts have been made by the company to improve the quality of internal communication to improve employee performance.